Upregulating HIF‐1α to Boost the Survival of Neural Stem Cells via Functional Peptides‐Complexed MRI‐Visible Nanomedicine for Stroke Therapy. Issue 23 (10th October 2022) - Wang, Zhe; Cai, Yujun; Zhang, Qinyuan; Li, Jianing; Lin, Bingling; Zhao, Junya; Zhang, Fang; Li, Yunhua; Yang, Xieqing; Lu, Liejing; Shuai, Xintao; Shen, Jun
Abstract: Neural stem cells (NSCs) transplantation has been considered as a promising strategy for the treatment of ischemic stroke. However, the therapeutic prospect is limited by the poor control over the survival, migration, and maturation of transplanted NSCs. Upregulating hypoxia inducible factor (HIF)‐1 α expression in stem cells can improve the survival and migration of NSCs grafted for stroke therapy. Functional peptide drugs, which could inhibit endogenous HIF‐1 α ubiquitination, might be used to effectively upregulate the HIF‐1 α expression in NSCs, thereby to improve the therapeutic effect in ischemia stroke. Herein, a magnetic resonance imaging (MRI)‐visible nanomedicine is developed to codeliver functional peptides and superparamagnetic iron oxide (SPIO) nanoparticles into NSCs. This nanomedicine not only promotes the survival and migration ability of NSCs but also allows an in vivo tracking of transplanted NSCs with MRI. The results demonstrate the great potential of the functional peptides‐complexed multifunctional nanomedicine in boosting the therapeutic effect of stem cell‐based therapy in stroke. Abstract : Labeling neural stem cells (NSCs) with superparamagnetic iron oxide (SPIO)‐loaded, methoxy‐polyethylene glycol (mPEG)‐modified tetraethylenepentamine (TEPA) and cholic acid (CA)‐based micelles (PTC) can promote the survival and migration of NSCs via upregulation of hypoxia inducible factor‐1 α (HIF‐1 α ). This magnetic resonance imaging (MRI)‐visible nanomedicine can enhance the therapeutic effect and allow in vivo MRI tracking of NSCs in a mouse model of acute stroke.